Microgravity Two-phase Flow and Heat Transfer - Gabriel, Kamiel S. (Space Technology Library, 2007)
Multiphase thermal systems (involving more than one phase or one component) have numerous applications in aerospace, heat-exchanger, transport of contaminants in environmental systems, and energy transport and energy conversion systems. Advances in understanding the behaviour of multiphase thermal systems could lead to higher efficiency energy production systems, improved heat-exchanger design, and safer and enhanced treatment of hazardous waste. But such advances have been greatly hindered by the strong effect of gravitational acceleration on the flow. Depending on the flow orientation and the phase velocities, gravitational forces could significantly alter the flow regime, and hence the pressure-drop and heat-transfer coefficients associated with the flow. A reduced gravity environment (or "microgravity"), provides an excellent tool to study the flow without the masking effects of gravity. This book presents for the first time a comprehensive coverage of all aspects of two-phase flow behaviour in the virtual absence of gravity.